2020
DOI: 10.1111/jocs.15210
|View full text |Cite
|
Sign up to set email alerts
|

Bicuspid aortic valve sparing root replacement

Abstract: Background and Aim of Study: Mid and long-term data regarding the durability of bicuspid aortic valve sparing root replacement is not completely understood. In this study, our institutional experience is reviewed regarding this procedure with special attention to the operative technique. Methods: From 2004 to 2019, 1241 patients underwent aortic root replacement and of these 79 patients underwent bicuspid aortic valve sparing root replacement. Early and late outcomes along with echocardiographic data were revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…We did, however, find a relatively frequent occurrence of type 0 (29.4%) compared to rates that Sievers et al reported (7%) 21 . Regarding intra‐ and postoperative outcomes, our data are in line with reports from other groups and confirm that AVSRR, such as the Tirone procedure, can be performed in patients with BAV with very low perioperative risks for morbidity and mortality (0%–2.5%) 8,11–13,16 . Most of our patients had elective surgery for the Tirone procedure without other associated surgery to exclude confounding from other procedures.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We did, however, find a relatively frequent occurrence of type 0 (29.4%) compared to rates that Sievers et al reported (7%) 21 . Regarding intra‐ and postoperative outcomes, our data are in line with reports from other groups and confirm that AVSRR, such as the Tirone procedure, can be performed in patients with BAV with very low perioperative risks for morbidity and mortality (0%–2.5%) 8,11–13,16 . Most of our patients had elective surgery for the Tirone procedure without other associated surgery to exclude confounding from other procedures.…”
Section: Discussionsupporting
confidence: 89%
“…21 Regarding intra-and postoperative outcomes, our data are in line with reports from other groups and confirm that AVSRR, such as the Tirone procedure, can be performed in patients with BAV with very low perioperative risks for morbidity and mortality (0%-2.5%). 8,[11][12][13]16 Most of our patients had elective surgery for the Tirone procedure without other associated surgery to exclude confounding from other procedures. Holmgren et al however, still reported that even combined surgery was not associated with higher observed or relative mortality.…”
Section: Follow-up Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past years, a modified surgical technique offers BAV patients with root aneurysms to replace the dilated segment while preserving the valvular components ( 3 ). The VSARR was associated with lower surgical complications such as heart block and cerebral hemorrhage and had a higher survival rate than the traditional Bentall surgical procedure, which also uses replacement of the aortic valve ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The supracoronary aortic prosthesis with the "full root" technique is a complete cross-section of the aortic diameter, removal of the dissected area of the ascending aorta and placement of the prosthesis of the ascending aorta above the coronary arteries (approximately 1.5-2 cm), as high as possible to the place of discharge of the brachiocephalic artery with inserting circular (3600) anastomoses, without preserving the posterior wall of the ascending aorta, using the principles of the "free tension technique" (18). The supracoronary prosthesis of the ascending aorta is performed when there are no additional dissections of the intima in the projection of the aortic root (the sinuses of Valsalva, coronary arteries ostia), with no hemodynamically significant pathologies of the aortic valve, in patients without annulo-aortic ectasia (19) and without additional ruptures of the aortic intima in the zone of the aortic arch.…”
Section: Discussionmentioning
confidence: 99%